2012
DOI: 10.3892/ol.2012.1004
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of complete response by MRI following neoadjuvant chemotherapy predicts pathological tumor responses differently for molecular subtypes of breast cancer

Abstract: Abstract. In the present study, clinical tumor response following neoadjuvant chemotherapy (NAC) was diagnosed by magnetic resonance imaging (MRI) and clinicopathological factors, including molecular subtypes at baseline, were analyzed for correlations with pathological tumor responses. In addition, clinicopathological factors were analyzed for a correlation with the MRI capacity to predict pathological complete response (pCR). Clinical tumor response evaluated by MRI following NAC was determined as a clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 16 publications
5
36
0
1
Order By: Relevance
“…Recent studies have shown that the accuracy of imaging in clinical response evaluation varies by breast cancer subtype according to HR and HER2 status (11)(12)(13)(14)(15)(16)(17)(18)(19). Specifically, MRI more accurately predicts pathologic response in HR-negative subtypes rather than HRpositive stubtypes (11,(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…Recent studies have shown that the accuracy of imaging in clinical response evaluation varies by breast cancer subtype according to HR and HER2 status (11)(12)(13)(14)(15)(16)(17)(18)(19). Specifically, MRI more accurately predicts pathologic response in HR-negative subtypes rather than HRpositive stubtypes (11,(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…In literature, a wide spread of NPVs has been described in the HER2-positive subtype ranging from 0 to 95% in studies providing clear definitions of accuracy measurements and including C25 patients [6,7,9,10,14,17,18]. This variation Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Whilst the definition of pCR varies in different studies, investigators have shown that accuracy of MRI for predicting pCR varies with different subtypes [5,6,23]. Loo et al [4] found excellent correlation between residual tumour size on MRI and post treatment surgical size for TN and HER2+ subtypes, but not for Luminal cancers.…”
Section: Discussionmentioning
confidence: 99%
“…They found highest negative predictive value (the ability to predict pCR) with TN and HER2+ cancers. Hayashi et al [5] evaluated 264 breast cancers and found highest discrepancy between imaging and pathology for Luminal cancers and cautioned when interpreting MR images in Luminal cancers, with underestimation of disease in two-thirds of them. In our study, MR underestimated disease in 17 (58.6%) Luminal cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation